Mathematical entrepreneurship in educational institutions (2019)
In the present investigation, a reflection was made on the teaching practices in the area of mathematics that entails educational institutions conducive academic spaces to generate entrepreneurial attitudes in students. These are personalized from the voices of the participants, involving the student in the development of the entrepreneurial culture and in the basic competences generated from the mathematics. The complexity present in the teaching practice becomes significant in the student when it is possible to establish an interrelation with their social, cultural, economic environment and, above all, in the proactive action that the student develops in the face of any situation in life. A new feeling that allows manifestations in students of: autonomy, responsibility, innovation, creativity and to generate in them citizen awareness.